2019
DOI: 10.1016/j.radcr.2019.02.018
|View full text |Cite|
|
Sign up to set email alerts
|

Relapsed multiple myeloma manifesting as extramedullary plasmacytoma of the breast: Imaging findings

Abstract: Extramedullary plasmacytoma of the breast (EPB), a manifestation of multiple myeloma (MM), is very rare. It is important to recognize the imaging findings of EPB because it may be the first manifestation of relapsed MM. An 85-year-old woman presented with a lump in her right breast 4 years after the complete remission of MM. She underwent mammography and ultrasonography, which showed an oval circumscribed mass and an irregular circumscribed heterogeneous solid mass, respectively. Following ultrasound-guided va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
(17 reference statements)
1
10
0
Order By: Relevance
“…However, there are few reports about the CT findings of breast plasmacytoma. 20 Previous studies on other body parts have indicated that the imaging features of MM were nonspecific, 19 most extramedullary plasmacytomas were generally demonstrated as well-defined soft-tissue mass with homogeneous enhancement on CT examination, which was consistent with the breast mass in our patient.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…However, there are few reports about the CT findings of breast plasmacytoma. 20 Previous studies on other body parts have indicated that the imaging features of MM were nonspecific, 19 most extramedullary plasmacytomas were generally demonstrated as well-defined soft-tissue mass with homogeneous enhancement on CT examination, which was consistent with the breast mass in our patient.…”
supporting
confidence: 80%
“…18 In addition, microcalcification was extremely rare in MM. 19 There are various posterior features, and the most common feature is posterior acoustic enhancement, followed by no posterior acoustic transmission, while posterior acoustic shadowing is very rare. In our patient, both the breast and chest wall masses showed posterior enhancement.…”
mentioning
confidence: 99%
“…Because mammography, US, and MRI findings may not be diagnostic, the differential diagnosis for primary carcinoma, other lymphoproliferative diseases, and even benign masses depends on histopathological evaluation [4]. Breast MM/plasmacytoma treatment depends on the systemic extent of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…MM can affect extraosseous sites as solitary lesions (extramedullary plasmacytoma) or as a presentation of MM relapse in less than 5% of cases. Moreover, MM in the breast has been rarely documented [24]; the first case of MM in the breast was reported in 1925 [4]. Since then, only 20 other patients with breast involvement have been documented in the literature till date [5].…”
Section: Introductionmentioning
confidence: 99%
“…Breast involvement is rare, with approximately 63 cases reported worldwide between 1928 to 2009 [2]. The study authors found an additional 20 published reports in the literature between 2009 to 2019, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], with two retrospective institutional reviews [15,16]. Additionally, Surov et al conducted a comprehensive review of prior case reports and patients at their institution between 1997-2009, finding that 15% of breast plasmacytomas were primary lesions while 85% involved multiple myeloma [23].…”
Section: Etiology and Demographicsmentioning
confidence: 99%